A novel in-vivo phagocytosis assay to gain cellular insights on sponge-microbe interactions - Marulanda-Gomez, Angela M.; Bayer, Kristina; Pita, Lucia; Hentschel, Ute (Frontiers in Marine Science, 2023)
Introduction Sponges harbor diverse, specific, and stable microbial communities, but at the same time, they efficiently feed on microbes from the surrounding water column. This filter-feeding lifestyle poses the need to distinguish between three categories of bacteria: food to digest, symbionts to incorporate, and pathogens to eliminate. How sponges discriminate between these categories is still largely unknown. Phagocytosis is conceivable as the cellular mechanism taking part in such discrimination, but experimental evidence is missing. We developed a quantitative in-vivo phagocytosis assay using an emerging experimental model, the sponge Halichondria panicea. Methods We incubated whole sponge individuals with different particles, recovered the sponge (host) cells, and tracked the incorporation of these particles into the sponge cells. Fluorescence-activated cell sorting (FACS) and fluorescent microscopy were used to quantify and verify phagocytic activity, defined here as the population of sponge cells with incorporated particles. Sponges were incubated with a green microalgae to test if particle concentration in the seawater affects the percentage of phagocytic activity, and to determine the timing where the maximum of phagocytic cells are captured in a pulse-chase experiment. Lastly, we investigated the application of our phagocytic assay with other particle types (i.e., fluorescently-labelled bacteria and fluorescent beads). Results and discussion The percentage of sponge cells that had incorporated algae, bacteria, and beads ranged between 5 to 24%. These phagocytic sponge cells exhibited different morphologies and sizes depending on the type of particle presented to the sponge. Particle incorporation into sponge cells was positively related to algal concentration in the seawater, suggesting that sponge cells adjust their phagocytic activity depending on the number of particles they encounter. Our results further revealed that sponge phagocytosis initiates within minutes after exposure to the particles. Fluorescent and TEM microscopy rectified algal internalization and potential digestion in sponge cells. To our knowledge, this is the first quantitative in-vivo phagocytosis assay established in sponges that could be used to further explore phagocytosis as a cellular mechanism for sponges to differentiate between different microorganisms.